Effectiveness of Sajie Care Application in Reducing Stress: A Quasi-Experimental Study - Isymiarni Syarif; Hasnawati Amqam; Saidah Syamsuddin (The Indonesian Institute of Science and Technology Research, 2026)
This study evaluated the effectiveness of the Sajie Care mobile application in reducing stress among caregivers of individuals with schizophrenia. A quasi-experimental pretest–posttest control group design was conducted with 64 caregivers in Labakkang Sub-district, South Sulawesi, Indonesia. Participants were divided into an intervention group using the Sajie Care app (n = 32) and a control group receiving leaflet-based psychoeducation (n = 32). The three-month intervention integrated stress management education, Spiritual Emotional Freedom Technique (SEFT) therapy, medication reminders, and peer support. Stress levels were assessed using the Indonesian version of the Perceived Stress Scale (PSS-10). The intervention group showed a significant reduction in mean stress scores from 17.84 to 13.06 (p < 0.001), while the control group showed a smaller, non-significant change (16.84 to 15.75; p = 0.070). Between-group analysis confirmed significant differences at posttest 3 (p = 0.014). These findings indicate that Sajie Care effectively reduces caregiver stress and enhances coping capacity compared to conventional psychoeducation. The study demonstrates the potential of culturally adapted mobile health interventions as accessible, sustainable tools to strengthen community-based mental health services in low-resource settings.